Acute kidney injury in cirrhosis: implications for liver transplantation. Issue 2 (April 2019) - MacDonald, Andrew J.; Nadim, Mitra K.; Durand, François; Karvellas, Constantine J.
Abstract : Purpose of review: Acute kidney injury (AKI) in cirrhosis consists of varying phenotypes, with hepatorenal syndrome (HRS) representing a single entity. Prompt recognition and diagnosis of AKI cause identifies appropriate therapeutic measures. This review provides an overview of AKI definitions, highlights challenges in quantifying renal impairment in cirrhosis, lists novel diagnostic AKI biomarkers, and summarizes transplantation implications. Recent findings: Biomarkers (neutrophil gelatinase-associated lipocalin, kidney injury molecule-1, interleukin-18, and liver-type fatty acid-binding protein) may assist in the identification of underlying acute tubular necrosis. Of these, neutrophil gelatinase-associated lipocalin is the most promising; however, significant overlap occurs among AKI phenotypes, with diagnostic values yet to be defined. Mainstay treatment of HRS consists of albumin and vasopressors. Acute-on-chronic liver failure grade independently predicts response to terlipressin treatment. Many end-stage liver disease patients with AKI have underlying chronic kidney disease with important implications on pre and postliver transplantation mortality. Simultaneous liver–kidney transplant candidacy is based on low likelihood of renal recovery. Summary: Novel biomarkers may assist in identification of acute tubular necrosis and persistent/severe AKI. Norepinephrine has been suggested to be inferior to terlipressin, with additional research required. Increasing acute-on-chronic liver failure grade correlates with lower likelihood of vasopressor response in HRS. Severe preliver transplantation AKI confers significantly worse postliver transplantation renal outcomes.